Bonheur et unification des vertus chez Aristote - Natali, Carlo (Journal of Ancient Philosophy, 2007)
The main problem studied here is the Aristotelian doctrine of the unity of virtues. Aristotleaccepts a variety of virtues, moral and intellectual, and has consequently to contend with theproblem of their occasionally being disconnected from one another. He has differentstrategies to deal with this problem; in Eudemian Ethics, he unites them by particular andpsychological ways, whereas in Nicomachean Ethics their unity is mainly brought about bytheir connection to the perfect and best life. The unification works at various levels: inNicomachean Ethics Aristotle is mainly interested in unifying the virtues of character,whereas in Eudemian Ethics he unifies all virtues in the concept of kalokagathia. Thesedifferent strategies do not call for a genetic explanation, for they are all compatible with oneanother; in fact, they make more noticeable several aspects of the same problem.